The Oxycaryum cubense floating mat as refuge of Cornops aquaticum (Orthoptera: Acrididae), a new control agent of the water hyacinth - Franceschini, Maria Celeste (2011)
Cornops aquaticum is a native Neotropic grasshopper frequently associated with Eichhornia (Pontederiaceae) spp. The aims of this research are: (1) to report the presence of this grasshopper on Oxycaryum cubense (Cyperaceae) in relation to climate conditions and microhabitat structure; and (2) to study and compare survivorship and occurrence of feeding and oviposition of C. aquaticum on O. cubense and the host plant (E. azurea). Grasshopper abundance was recorded during all seasons in both plants; field observations and no-choice tests were conducted to analyze the survivorship, feeding and oviposition of C. aquaticum on both plants. Results show that C. aquaticum is not able to feed and oviposit on O. cubense, but rather uses this macrophyte as refuge under specific climate conditions.